Emerging Issues in Participatory forest Management - Pratima; Jattan, S. S. (Indian Forester, 2002)
Implementation of Joint Forest Management (JFM) in the country has highlighted several issues which need to be addressed to ensure its success. The paper discusses important issues emerging out of JFM programme implementation which include: (i) appropriate mechanism of participation between the parties involved, (ii) institutionalisation of JFM programme, (iii) lack of clarity about JFM objectives, (iv) adequacy of benefits to village communities, (v) sustainability of JFM, and (vi) integration of JFM and rural development.